(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the emergence and development of philosophical thought in Persian-Tajik literature, with a special focus on the works of Abu Abdallah Rudaki - the great poet and thinker of the 9th–10th centuries. Rudaki is considered the founder of Tajik poetry and one of the earliest thinkers whose works reflect deep philosophical reflections on the nature of life, time, human existence, and moral values. The article examines key philosophical themes in his works, such as the transience of life, the significance of time, the interaction between humans and nature, as well as the ethical contemplation of society. Particular attention is given to how Rudaki used poetic form to express philosophical ideas, making them accessible to a wide audience. His works are imbued with profound thoughts on human destiny and spiritual quests, which had a significant influence on the development of Persian-Tajik literature and culture as a whole. The article also analyzes the philosophical ideas embedded in his poetry and their influence on later poets and thinkers, such as Omar Khayyam, Saadi, and Hafez. Furthermore, it explores the context in which Rudaki’s philosophical views were shaped, including the historical, cultural, and social factors of the Islamic Golden Age. The philosophical motifs in his works reveal a deep aspiration for wisdom, justice, harmony with nature, and reflection on the finitude of life - making his poetry relevant even in the modern era.